The Value of Investor Protection: Firm Evidence from Cross-Border Mergers - Bris, Arturo; Cabolis, Christos (Review of Financial Studies, 2008)
International law prescribes that in a cross-border merger where the acquiror buys 100 percent of the target, the target firm becomes a national of the country of the acquiror. Among other effects, the change in nationality implies a change in investor protection, because the law that is applicable to the newly merged firm changes as well. Therefore, cross-border mergers provide a natural experiment to analyze the effects of changes - both improvements and deteriorations - in corporate governance on firm value. We construct measures of the change in investor protection induced by cross-border mergers in a sample of 506 acquisitions from 39 countries, spanning the period 1989 to 2002. We find that the announcement effect of a cross-border merger for the target firm is higher - relative to a matching, domestic acquisition - the better the shareholder protection and the accounting standards in the country of origin of the acquiror. This result is only significant in acquisitions where the acquiror buys 100 percent of the target, and therefore where the nationality of the target firm changes. In addition, this result is only significant when the acquiror comes from a more-protective country, which suggests that target firms avoid addopting weaker protection via private contracting. Interestingly, we do not find a symmetric effect on the acquiror's return. All in all, we present evidence that the transfer of better corporate governance practices through cross-border mergers is positively valued by markets with weaker corporate governance.